Yield and Chemical Composition of Tobacco Leaves of Different Cultivars as Affected by Four Levels of Potassium Chloride (Biological Sciences - PJSIR, 2006)
An outdoor pot experiment was conducted to evaluate response of ten tobacco (Nicotiana tabacum) cultivars to KCl induced chloride toxicity at the Tobacco Research Station, Mardan, Pakistan, during 2002. The study included four levels of KCl, which were: 0, 4, 8 and 12 mmol kg-1 soil and was arranged according to 4x10 factorial design with three replications. Seedlings of the respective cultivars, Spt-G.28, KHG-14, KHG-15, KHG-18, Coker-371 Gold, Candel, KHG- 19, K-399, Coker-48 and Coker-176 were planted in pots containing 5 kg normal soil. After establishment of the seed- lings, the respective amount of KCl was applied in one litre of water and then irrigated with normal water for the rest of the growing period. The data showed that all growth parameters increased with the initial dose of 4 mmol kg-1 of KCl, but then decreased with higher levels due to chloride toxicity. When averaged across cultivars, the highest seedling height (17.4 cm), number of leaves per plant (8.7), leaf area (42.0 cm2), and dry weight (10.17 g per pot) were recorded in treatments receiving 4 mmol KCl kg-1 soil. Chloride, reducing sugars, nicotine and K content of leaves showed linear regression with KCl levels (r2 > 0.95), producing 250, 74.33, 18.62 and 14.14% increase at 12 mmol kg-1 soil, respectively, as compared to control. Nitrogen content of leaves also increased with increasing KCl levels in most of the cultivars showing an overall increase of 12.46%, as compared to control. Unlike other growth parameters, ash content increased with increase in KCl level up to the higher dose of 12 mmol kg-1 soil. Cultivars showed differential response to the KCl induced chloride toxicity. KHG-14 was found to be the most sensitive cultivar regarding growth parameters, while KHG-18 and KHG-15 recorded higher changes in chemical composition to KCl application. Considering the overall performance, Spt-G.28 was found to be the most suitable variety producing higher plant height, number of leaves per plant, leaf area, fresh and dry weight, reducing sugars and nicotine, and lower levels of nitrogen and chloride as compared to other cultivars. It is concluded that KCl applications should be avoided or applied very carefully to prevent its adverse effects on yield and quality of tobacco as our soils already contain sufficient amount of chlorides.